2014
DOI: 10.1007/s00464-014-3640-5
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic suture fixation of self-expanding metallic stents with and without submucosal injection

Abstract: Endoscopic suture fixation of SEMS resulted in a statistically significant increase in pullout force necessary to displace the stents. Submucosal injection prior to suture fixation preserves the increased pullout force while minimizing the risk of transmural penetration with the potential for less risk of injury to mediastinal structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Its occurrence delays leak closure increases the number of endoscopic procedures, and, consequently, increases the likelihood of severe adverse events. Several alternatives, including stent fixation with placement of metal clips or endoscopic suture, have been reported to prevent stent migration [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Its occurrence delays leak closure increases the number of endoscopic procedures, and, consequently, increases the likelihood of severe adverse events. Several alternatives, including stent fixation with placement of metal clips or endoscopic suture, have been reported to prevent stent migration [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have demonstrated that fixation significantly reduces migration. Two studies involving porcine models found that endoscopic sutures increased the force necessary to dislodge inserted SEMS, 19,20 while another 2 showed a reduction due to fixation in the clinical setting. 21,22 Furthermore, a recent randomized controlled study by Wang et al 16 found that stent fixation with metal clips is effective in preventing stent migration.…”
Section: Discussionmentioning
confidence: 99%
“…Wilcox et al hypothesized that a submucosal injection of saline may decrease migration and further mitigate the theoretical (but as of yet unobserved) risk of perforation or injury to periesophageal structures. Using 15 porcine explants and submucosal injections of 3-5 cc of saline/methylene blue solution with an endoscopic injection needle (Carr Locke Sclerotherapy Needle, US Endoscopy, Mentor, OH), they demonstrated that pull out forces of sutured SEMS were greater in the injected paradigm compared to a sutured SEMS alone [19]. Intriguingly, the same augmentation was not replicated with endoscopic clips instead of sutures.…”
Section: Suturingmentioning
confidence: 99%